Holistic evaluation of long‐term earthworm field studies with a fungicide. (16th December 2021) - Jänsch, Stephan; Braaker, Sonja; Römbke, Jörg; Staab, Frank; Pamminger, Tobias
Abstract: Plant protection products to be placed on the market in the European Union need to meet rigorous safety criteria including the testing of lumbricid earthworms, the functionally most important soil organism group in Central European agricultural ecosystems. To address uncertainties and investigate the potential long‐term in‐crop effects of the fungicide Cantus ® containing 50% boscalid as an active substance, a series of standardized earthworm field studies with an overall duration of 5 years per study program was carried out in four German agricultural fields under realistic crop rotation conditions. A two‐step approach was chosen to analyze the potential overall long‐term effects on earthworms in agricultural fields: (i) an assessment of the earthworm abundance development in the course of the four study programs in relation to the determined actual content of boscalid in soil and (ii) an effect size meta‐analysis of earthworm abundance 1 year after treatment for each consecutive year and study program. Measured boscalid concentrations in the soil after multiple applications were well above the maximum boscalid residues observed in agricultural soils across Central Europe. There were isolated statistically significant reductions of earthworm abundance for some species and groups at some time points during the studies, but no consistent relationship to the Cantus ® treatments was observed. These results were supported by the meta‐analysis, indicating no adverse effects on earthworm populations. Therefore, fluctuations of abundance reflect the natural variation of the populations rather than a concentration‐related response. Based on this comprehensive analysis, we conclude that there is no application rate‐related effect of the 5‐year use of Cantus ® on the development of the earthworm communities. The four study programs, paired with a comprehensive evaluation, directly address the concerns about the potential long‐term effects of boscalid on earthworms in the field and suggest that multiyear applications do not adversely affect earthworm populations. Integr Environ Assess Manag 2022;18:1399–1413. © 2021 ECT Oekotoxikologie GmbH and BASF SE. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: A series of standardized earthworm field studies with the fungicide Cantus ® containing 50% boscalid as active substance and with an overall duration of 5 years per study program was carried out in four German agricultural fields under realistic crop rotation conditions. The development of earthworm abundance in the course of the four study programs in relation to the determined actual content of boscalid in soil was assessed and an effect size meta‐analysis of earthworm abundance one year after treatment for each consecutive year and study program was performed. Measured boscalid concentrations in soil after multiple applications were well above the maximum boscalid residues observed in agricultural soils across Central Europe. The four study programs, paired with a comprehensive evaluation, directly address the concerns about potential long‐term effects of boscalid on earthworms in the field and suggest that multiyear applications do not adversely affect earthworm populations.